CURRENT APPROACHES TO HEALTH-PRESERVING ACTIVITIES OF PHYSICAL CULTURE SPECIALISTS IN THE CONTEXT OF INTEGRATION INTO THE GLOBAL EDUCATIONAL SPACE - Sogokon, О.А.; Donets, О.V.; Khomenko, P.V.; Myronenko, S.G.; Shostak, Ye.Yu. (World of Medicine and Biology, 2025)
The article is devoted to the urgent problem of using modern approaches to health-preserving activities of physical culture specialists in the context of integration into the global educational space. The structure of health-preserving competence of a physical culture specialist includes: multifunctionality, which helps to solve the problems of youth health preservation in the space of health components (physical, social, mental and spiritual); interdisciplinarity, which provides information about a healthy lifestyle in all areas of education, studies ways and means of health preservation; multidimensionality, because it considers the essence of human health as a holistic, multidimensional phenomenon. We have proven that the health-preserving activities of physical culture specialists are a set of measures aimed at preserving and strengthening the health of young athletes. In this study, we developed and experimentally tested a model for implementing health-preserving technologies in the professional training of education seekers on the basis of the Poltava National Pedagogical University named after V.G. Korolenko.
Keywords: health-preserving activities; modern approaches; physical education specialist; integration; educational space